Tectono-thermal events of the North Qilian Orogenic Belt, NW China: Constraints from detrital zircon U-Pb ages of Heihe River sediments. (1st May 2017) - Gong, Hujun; Zhao, Hui; Xie, Wenbin; Kang, Weidong; Zhang, Rui; Yang, Lirong; Zhang, Yunxiang; Song, Jiangyu; Zhang, Yaqin
Graphical abstract: Highlights: More than 1000 U-Pb ages of detrital zircon grains from Heihe River sediments are presented. Detrital zircon grains from Heihe River sediments were mainly sourced from the North Qilian Orogenic Belt. The formation of the North Qilian Orogenic Belt was related to the evolution of the Paleo-Tethys Ocean. Abstract: The ∼800 km long Heihe River in northwestern China originates from the North Qilian Mountain, and passes through the Beishan Mountain before it reaches the Juyanhai Lake. Geologically, the river crosscuts the North Qilian Orogenic Belt, the Alax Terrane, and the Beishan Orogenic Belt. LA-ICP-MS U-Pb dating of detrital zircon from Heihe River sediments shows four age groups: 2700–1700 Ma, 1700–650 Ma, 650–358 Ma, and 358–230 Ma, and age peaks at ∼2450 Ma, ∼1850 Ma, ∼950 Ma, ∼520 Ma, 505 Ma, ∼480 Ma, ∼450 Ma, ∼430 Ma, ∼380 Ma, ∼320 Ma, and ∼295 Ma. The age distribution patterns indicate that Heihe River sediments were mainly sourced from the North Qilian Orogenic Belt. The detrital zircon ages demonstrate that the North Qilian Orogenic Belt may have Archean to late Paleoproterozoic rocks. Several tectonothermal events are also identified: opening of the North Qilian Ocean (part of the Paleo-Tethys Ocean) at early Neoproterozoic, subduction of oceanic lithosphere and formation of a trench-arc-basin system at late Neoproterozoic to late Ordovician, closure of the oceanic basin at late Ordovician, and collision of the Qaidam and Alax terranes at early Devonian. Our study indicates that the formation of the North Qilian Orogenic Belt was mainly related to the formation and closure of the Paleo-Tethys Ocean.